Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis

Nanotrap infused ultrathin hybrid composite material for rapid and highly selective entrapment of 99TcO4- - Mandal, Writakshi; Fajal, Sahel; Majumder, Dipanjan; Sengupta, Arijit; Let, Sumanta; Urkude, Rajashri R.; Shirolkar, Mandar M.; Torris, Arun; Ghosh, Sujit K. (CHEMICAL SCIENCE, 2024)
Keywords: Adsorption; CAPTURE; EFFICIENT; Metal-organic framework; Removal; TECHNETIUM

Role of nitrogen doping in modulating ruthenium nanocatalysts for enhanced electrochemical hydrogen evolution reaction in alkaline medium - Korampattu, Lavanya; Barik, Sidharth; Pandikassala, Ajmal; Urkude, Rajashri R.; Kurungot, Sreekumar; Dhepe, Paresh L. (Chemistry of Materials, 2024)
Nitrogen doping has become a fundamental approach to enhance the catalytic performance of carbon materials across various applications. The introduction of nitrogen creates defects and active sites, promoting the formation of small metal particles and strengthening the metal-support interaction within carbon materials. However, the challenge lies in developing sustainable and cost-effective methods for synthesizing nitrogen-doped carbon materials. In this study, we present a sustainable approach for the synthesis of ruthenium on nitrogen-doped carbon catalysts (Ru-CCP) using chitosan as a nitrogen and carbon source. Unlike traditional methods, our process avoids the use of additional nitrogen precursors and templates, streamlining the synthesis while using a renewable resource. The synthesized material exhibits an exceptional performance in the electrochemical hydrogen evolution reaction (HER) in alkaline conditions by achieving a current density of 25 mA cm(-2) at an impressively low overpotential of 46 mV, outperforming Pt/C under similar conditions. The detailed studies on structural and electronic properties of the materials using X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and transmission electron microscopy (TEM) revealed that the remarkable catalytic activity is upheld by the unique interplay between Ru delta+ and surface nitrogen moieties, notably pyridinic and pyrrolic nitrogen. Here, we demonstrate the control of particle size and electronic environment around the metal atom via the interaction of nitrogen and unravel the role of nitrogen doping in tuning the catalytic performance. In addition, this work offers insights into efficient HER catalyst design and emphasizes the potential of biomass-derived materials like chitosan in advancing clean hydrogen production for renewable energy applications.

Transient Electro-Graphitization of MOFs Affecting the Crystallization of Ruthenium Nanoclusters for Highly Efficient Hydrogen Evolution - Karim, Golam Masud; Patra, Amalika; Deb, Sujit Kumar; Upadhya, Hemanta; Das, Snehasish; Mukherjee, Priyam; Ahmad, Waleed; Barman, Narad; Thapa, Ranjit; Dambhare, V, Neha; Rath, Arup Kumar; Das, Jaysri; et al. (ADVANCED FUNCTIONAL MATERIALS, 2024)
Keywords: amorphous ruthenium; crystallization control; graphitic nanostructure

Atomically dispersed Co-Cu dual active sites in carbon networks as an efficient oxygen electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Urkude, Rajashri R.; Ahmed, Tanbir; Ghosh, Biplab; Roy, Poulomi (Dalton Transactions, 2025)
Single-atom metal-based electrocatalysts offer extended advantages by maximizing the utilization of active sites but often suffer from complex synthesis processes and low-density metal loading. The present work showcases a strategic design for integrating highly dense cobalt-copper dual atoms dispersed on a nitrogen-rich porous carbon network (CoCu-NGC). The atomically dispersed CoCu-NGC outperforms the ORR and OER activities of their single metallic counterparts (Co-NGC or Cu-NGC) and conventional noble-metal based electrocatalysts (Pt/C and RuO2). Benefitting from the electronic modulation in the dual SAC system, the CoCu-NGC displayed outstanding bifunctional performance with low Delta E values of 0.69 V in freshwater and 0.78 V in seawater, highlighting it as a potential alternative to the costly state-of-art electrocatalysts.

Deciphering the intricate mechanisms behind the selective oxidation of methane to C1 and C2 oxygenates over FeAu/γ-Al2O3 catalysts - Prabu, Marimuthu; Manikandan, Marimuthu; Rengam, B. Sathya Sai; Ramakrishnan, Archana; Raja, Abhishekram; Urkude, Rajashri R.; Ghosh, Biplab; Varghese, Jithin John; Raja, Thirumalaiswamy (Chemical Engineering Journal, 2025)
In this work, we demonstrate an eco-benign synthesis protocol for preparing gold nanoparticles and the role of the strong interaction between gold nanoparticles and iron oxide in FeAu/gamma-Al2O3 catalysts that render it an anionic (Au delta-) character while tailoring them in a smaller size. The multifunctional FeAu/gamma-Al2O3 catalyst selectively produces ethanol (95 % selectivity, similar to 240 mu mol(-1) cat) at a mild temperature of 75 degrees C without the addition of co-reactants during liquid phase methane oxidation with molecular oxygen. Conversely, Au/gamma-Al2O3 and Fe/gamma-Al2O3 catalysts exhibited high selectivity for CH3OH and HCHO. A high dispersion accompanied by strong electronic interaction between the Au delta–FeOx, as corroborated by diverse techniques, enables methane activation across the interface and coupling on the gold nanoparticles, which are responsible for the markedly improved formation of ethanol. Furthermore, in situ DRIFTS studies and DFT investigations point to a reaction mechanism of coupling of CH2OH and CH3 intermediates as the most likely route for ethanol formation.
Keywords: Anionic gold catalysts; Au-FeOx synergism; C-H bond activation; Ethanol; Methane oxidation; Methanol

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy

Dynamic and resilient cobalt copper nitride and iron nitride heterostructure aided energy economic urea electrolysis in anion exchange membrane electrolyzer - Sinha, Nibedita; Das, Chandni; Er, Chen-Chen; Urkude, Rajashri R.; Pal, Santanu; Ghosh, Biplab; Chai, Siang-Piao; Roy, Poulomi (Small, 2026)
Urea oxidation reaction (UOR) is recognized for energy-efficient hydrogen production, which nonetheless requires a meticulously designed electrocatalyst with active sites for intermediates adsorption and gaseous products desorption to fully exploit its advantages. Herein, we design the heterostructure consisting of cobalt copper nitride and iron nitride (Co3CuN/FexNy) as an efficient and trifunctional electrocatalyst, which requires 1.35 VRHE, 1.55 VRHE, and 0.23 VRHE potentials to reach 100 mA cm-2 current density for UOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER), respectively. Unlike the conventional UOR selective electrocatalyst, Co3CuN/FexNy not only facilitates the UOR -> OER switching but also shows self-regulatory ability in UOR <-> OER. The Density Functional Theory (DFT) study explained that while Co3CuN promoted the adsorption of CO(NH2)2 and H2O, FexNy facilitated CO2 and N2 desorption, resulting in accelerated UOR and HER kinetics. The electrocatalyst also demonstrated outstanding performance in a urea-coupled AEM electrolyzer with about 20% of power saving and great electrolyzer efficiency, further highlighting its potential for industry-relevant applications.
Keywords: AEM electrolyzer; heterostructured electrocatalyst; reversible adaptability; urea oxidation; Water oxidation